1995
DOI: 10.1002/ijc.2910630502
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p21WAF1/CIP1 is heterogeneous and unrelated to proliferation index in human ovarian carcinoma

Abstract: The growth-inhibitory protein p21WAF1/CIP1 is a potent inhibitor of various cyclin-dependent kinases, the expression of which is regulated at the transcriptional level by p53-dependent and -independent mechanisms. We examined p21WAF1/CIP1 mRNA and protein expression in 5 human ovarian-adenocarcinoma cell lines, 1 primary culture of normal surface epithelium and 17 human ovarian-tumor specimens. In culture cells, the p21WAF1/CIP1 protein was expressed in normal ovarian epithelial cells and at a high level in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…Any degree of p21/WAF1 positivity was observed in 74% of the tumours, and intense positive signals in 30% of the cases. These figures are consistent with those reported in a few previous studies, where p21/WAF1 expression was detected in 7-75% of the ovarian tumours (Barboule et al, 1995;Auer et al, 1996;Lukas et al, 1997;Werness et al 1997). Shigemasa et al (1997) studied the p21/WAF1 mRNA expression in 13 ovarian tumours and they found p53 mutation in 69% of tumours underexpressing p21 mRNA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Any degree of p21/WAF1 positivity was observed in 74% of the tumours, and intense positive signals in 30% of the cases. These figures are consistent with those reported in a few previous studies, where p21/WAF1 expression was detected in 7-75% of the ovarian tumours (Barboule et al, 1995;Auer et al, 1996;Lukas et al, 1997;Werness et al 1997). Shigemasa et al (1997) studied the p21/WAF1 mRNA expression in 13 ovarian tumours and they found p53 mutation in 69% of tumours underexpressing p21 mRNA.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, some recent data indicate that p53-independent pathways may also lead to an increase in p21/WAF1 expression (Jiang et al, 1994;Michieli et al, 1994). In epithelial ovarian cancer, no correlation between p21/WAF1 expression and p53 or Ki-67 has been demonstrated so far (Barboule et al, 1995, Werness et al, 1997.…”
mentioning
confidence: 98%
“…p21 displays a selectivity toward the inhibition of CDK/cyclin complexes that are involved in the transition from the G 1 to the S phase and acts as a tumor suppressor. There is a lot of data that p21 is expressed at a higher level in gliomas, ovarian, or lung cancers, and this high level of p21 protein is not associated with any inhibition of cellular proliferation (35)(36)(37). Overexpression of p21 was also associated with malignancy in DMBA-induced ovarian tumors (38).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of its obvious association with terminal differentiation and senescence (Halevy et al, 1995;McLeod et al, 1995;Missero et al, 1995;Parker et al, 1995) the WAFI gene product p21 has been found to be expressed in several human tumours, such as breast (Ozcelik et al, 1995) and ovarian carcinoma (Barboule et al, 1995) and non-small cell lung cancer (Marchetti et al, 1996). First, a pronouniced heterogeneity of p2 1 expression, often within onie tulmoui as well as between different tum)ours of identical stage anid grade.…”
Section: Discussionmentioning
confidence: 99%
“…Although over-expression of p21 has been shown to suppress tumour formation Yang et al, 1995) and the absence of WAF1/p21 facilitates tumour formation in several animal tumour models (El-Deiry et al, 1995;Missero et al, 1996), surveys on a variety of human tumours have revealed the WAFI/p21 gene to be infrequently mutated (Shiohara et al, 1994;Gao et al, 1995;Watanabe et al, 1995). Instead, expression of p21 has been found in human tumours of different origin (Barboule et al, 1995;Ozcelik et al, 1995;Marchetti et al, 1996).…”
mentioning
confidence: 99%